PAEDIATRIC STANDARDISED CONCENTRATION INFUSIONS – A NATIONAL SOLUTION. Issue 9 (17th August 2016) - Howlett, Moninne; Curtin, Michael; Doherty, Dermot; Gleeson, Paula; Sheerin, Michelle; Breatnach, Cormac
Abstract : Aim: Wide scale implementation of paediatric standardised concentration infusions (SCIs) and the use of smart pump technology has been slow despite international safety agency recommendations. Implementation rates in European hospitals fall far below those in the United States, where for the last decade accreditation has been linked to implementation.1 2 Multidisciplinary collaboration is essential, with pharmacy input and the creation of a smart pump drug library recognised as often being limiting, yet crucial factors, to implementation.3 Following on from the successful development and implementation of a paediatric drug library of standardised concentrations in the paediatric intensive care unit (PICU), operating theatres and cardiac ward of a large tertiary children's hospital, a project was set up to further develop this library for use across multiple sites including paediatric acute transport services. Method: Post-implementation of the original SCI drug library in the single site paediatric hospital in 2012, a database was created to record proposals for amendments and expansion of that library. A cross-site multidisciplinary collaborative working group was established with representation from PICU pharmacists, intensivists, nursing and clinical engineering to progress multisite adoption of a standardised drug library. Differences in practices across sites were identified and resolved by consensus where possible. Unresolved differences were overcome by omission or 'hiding' of particular drug lines at individual sites until consensus could be reached for future updates. Legally binding agreements were drawn up between sites, in conjunction with the infusion pump vendors, to prevent any future deviations from the master library. Results: Cross-site collaboration over a number of months facilitated the successful amendment and extension of the original drug library to create a new master drug file. Individual site versions of this library, and the supporting documentation were created and disseminated. A change control management plan was developed and agreed upon. Conclusion: Cross-site collaboration is achievable in supporting the increased implementation of standardised concentration infusions. The standardisation of practices across sites maximises both human and financial resources, and has the potential to reduce medications errors as both patients and medical staff transfer across sites.